Sexually dimorphic perineuronal nets in the rodent and primate reproductive circuit. Issue 13 (9th June 2021) - Ciccarelli, Alessandro; Weijers, Dilys; Kwan, William; Warner, Claire; Bourne, James; Gross, Cornelius T.
Abstract: Perineuronal nets are extracellular glycoprotein structures that have been found on some neurons in the central nervous system and that have been shown to regulate their structural plasticity. Until now work on perineuronal nets has been focused on their role in cortical structures where they are selectively expressed on parvalbumin‐positive neurons and are reported to restrict the experience‐dependent plasticity of inhibitory afferents. Here, we examined the expression of perineuronal nets subcortically, showing that they are expressed in several discrete structures, including nuclei that comprise the brain network controlling reproductive behaviors (e.g., mounting, lordosis, aggression, and social defense). In particular, perineuronal nets were found in the posterior dorsal division of the medial amygdala, the medial preoptic nucleus, the posterior medial bed nucleus of the stria terminalis, the ventrolateral ventromedial hypothalamus and adjacent tuberal nucleus, and the ventral premammillary nucleus in both the mouse and primate brain. Comparison of perineuronal nets in male and female mice revealed a significant sexually dimorphic expression, with expression found prominently on estrogen receptor expressing neurons in the medial amygdala. These findings suggest that perineuronal nets may be involved in regulating neural plasticity in the mammalian reproductive system. Abstract : We analyzed the expression of the perineuronal nets (PNNs) in mouse and marmoset brain. We found that in both species, its expression is present in many subcortical regions and it is strongly associated with the reproductive circuit. We showed that males show higher level of PNNs than females and in the posterior dorsal division of the medial amygdala (MeApd) the PNN is surrounding cells positive for the estrogen receptor alpha (Esr1). These data suggest a new role of PNN in controlling innate behavior circuits and sexual dimorphism.